Unawareness and selective disclosure: The effect of school quality information on property prices - John Haisken-DeNew; Syed Hasan; Nikhil Jha; Mathias Sinning (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
The Australian Government launched the My School website in 2010 to provide standardised information about the quality of schools to the Australian public. This paper combines data from this website with home sales data for the state of Victoria to estimate the effect of the publication of school quality information on property prices. We use a difference-in-difference approach to estimate the causal effect of the release of information about high-quality and low-quality schools relative to mediumquality schools in the neighborhood and find that the release of information about high-quality schools increases property prices by 3.6 percent, whereas the release of information about low-quality schools has no significant effect. The findings indicate that many buyers are unaware of the relevance of school quality information and that real estate agents pursue a strategy of disclosing information about high-quality schools to increase the sales price. Results from a survey of Victorian real estate agents provide evidence in favor of this strategy. – – In 2010 startete die australische Regierung die My School website, um der australischen Öffentlichkeit standardisierte Informationen über die Qualität von Schulen zu liefern. Dieses Papier kombiniert Daten von dieser website mit Daten zum Verkauf von Wohneigentum in Victoria, um den Effekt der Veröffentlichung von Informationen über die Schulqualität auf Preise von Wohneigentum zu schätzen. Wir verwenden einen Differenzen-in-Differenzen-Ansatz, um den kausalen Effekt der Veröffentlichung von Informationen über Schulen mit hoher bzw. niedriger Qualität (im Vergleich zu mittlerer Qualität) zu ermitteln und finden dass die Veröffentlichung von Informationen über qualitativ hochwertige Schulen den Preis von Wohneigentum um 3,6 Prozent erhöht, während die Veröffentlichung von Informationen über qualitativ minderwertige Schulen keinen signifikanten Effekt hat. Die Ergebnisse weisen darauf hin, dass viele Käufer nicht wissen, dass Informationen über die Schulqualität relevant sind, und dass Makler die Strategie verfolgen, ausschliesslich Informationen über qualitativ hochwertige Schulen zu offenbaren, um den Verkaufspreis zu erhöhen. Ergebnisse einer Umfrage von Maklern bestätigen, dass Makler diese Strategie tatsächlich verfolgen.
Keywords: D82; D84; I24; R31; 330; school quality; housing markets; information asymmetry; public policy evaluation; difference-in-difference estimation